Comparative decline in funding of European Commission malaria vaccine projects: what next for the European scientists working in this field? - Thøgersen, Regitze L.; Holder, Anthony A.; Hill, Adrian VS; Arnot, David E.; Imoukhuede, Egeruan B.; Leroy, Odile (Malaria journal, 2011)
Since 2000, under the Fifth and subsequent Framework Programmes, the European Commission has funded research to spur the development of a malaria vaccine. This funding has contributed to the promotion of an integrated infrastructure consisting of European basic, applied and clinical scientists in academia and small and medium enterprises, together with partners in Africa. Research has added basic understanding of what is required of a malaria vaccine, allowing selected candidates to be prioritized and some to be moved forward into clinical trials. To end the health burden of malaria, and its economic and social impact on development, the international community has now essentially committed itself to the eventual eradication of malaria. Given the current tentative advances towards elimination or eradication of malaria in many endemic areas, malaria vaccines constitute an additional and almost certainly essential component of any strategic plan to interrupt transmission of malaria. However, funding for malaria vaccines has been substantially reduced in the Seventh Framework Programme compared with earlier Framework Programmes, and without further support the gains made by earlier European investment will be lost.